2010
DOI: 10.1016/j.ejcnurse.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Physical and Mental Health 6 Months After Coronary Artery Bypass Grafting A Cohort Study

Abstract: This study identified predictors that have an impact on CABG patients' HRQoL 6 months after surgery. These predictors could cause elevated risk for morbidity and mortality. Clinicians have the opportunity to improve the HRQoL of CABG patients by targeting counselling and/or interventions focusing on the identified predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…In support of these findings, we previously reported that adverse events after heart transplantation are related to HRQOL both early 36 and later 37 after heart transplantation. Similarly, post-operative complications were related to HRQOL early 38, 39 and later 40 after myocardial revascularization. Lastly, the relationship between the pre implant VAS score and change in the VAS score after implant has also been demonstrated in the cardiac surgical literature.…”
Section: Discussionmentioning
confidence: 94%
“…In support of these findings, we previously reported that adverse events after heart transplantation are related to HRQOL both early 36 and later 37 after heart transplantation. Similarly, post-operative complications were related to HRQOL early 38, 39 and later 40 after myocardial revascularization. Lastly, the relationship between the pre implant VAS score and change in the VAS score after implant has also been demonstrated in the cardiac surgical literature.…”
Section: Discussionmentioning
confidence: 94%
“…However, RTW after a long-term sick leave may be stressful and emotionally demanding because it can be associated with patients' reduced physical capacities or changes in their work employment, such as reduction in working hours or in job tasks, decrease in self-reported responsibility and involvement [7][8][9]. Several studies have investigated the health-related qua lity of life (HRQL) after cardiac interventions [10][11][12][13]. Most of these studies have found that predictors of HRQL after a heart surgery or coronary angioplasty were primarily psychological and not related to the illness severity [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have identified positive changes in patient’s physical health and mental health after CABG [21,24,26,35-38], although improvement in mental health is generally slower [24]. Previous studies also suggest a significant interplay between patient’s physical health and mental health [21,24-26,39-42]. Female patients often have poorer outcomes from CABG, compared to males [38,43], and younger age is associated with better post-operative HRQoL [22,42].…”
Section: Introductionmentioning
confidence: 99%